Moderation effect analysis of assimilator-explorer cognitive style in the relationship between big five personality and innovative work behavior - Pratiwi, Putri Bayu Gusti Megantari (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This research is aim to see the moderate effect of assimilator-explrorer cognitive styles on the relationship between big five personality and innovative work behavior. Methods: This quantitative study utilized a non-probability convenience sampling method involving 125 employees from a shipbuilding manufacturing company. Data were analyzed using descriptive statistics, Pearson correlation, One-Way ANOVA, and a simple regression test with the PROCESS macro by Hayes to examine the moderating effect. Findings: Effect of moderation is considered due to inconsistent relationship between the big five personality and innovative work behavior. Conclusion: The main results of this study were processed using regression test with a PROCESS macro from Hayes (2013) and accompanied by additional results that is correlation between variables and demography analysis. Four dimension of big five personality are significantly correlated with innovative work behavior, 1 dimension of big five personality is significantly correlated with assimilator-explorer cognitive style, and there is no correlation between assimilator-explorer cognitive style and innovative work behavior. Based on demography analysis, there is difference score on assimilator-explorer cognitive style by job tenure, work unit and education. Based on the regression test, there is moderation effect of assimilator-explorer cognitive style on neuroticism dimension personality and innovative work behavior F(3,121)=4.76, R²=0.03, b=-0.16, t(121)=-2.18 (p <0.05). Novelty/Originality of this article: This study is different from previous studies. Therefore, further research is strongly encouraged to understand the role of cognitive-asimilator-explorer style in moderating the five major personalities and innovative work behaviors.